Reducing anxiety in the foreign language classroom: A positive psychology approach. (October 2021) - Jin, Yinxing; Dewaele, Jean-Marc; MacIntyre, Peter D.
Abstract: This paper reports on a study that took a positive psychology approach to foreign language anxiety reduction. More specifically, it investigated whether reminiscing about language achievements could effectively diminish the learners' foreign language classroom anxiety. It also explored the patterns nested in the reminiscing process. To this end, 88 first language Chinese university students of English were randomly assigned into experimental (n = 43) and control groups (n = 45), who filled out a short-form anxiety scale before and after a 30-day intervention. The experimental group students were also requested to record what they had reminisced about as well as their emotional experiences during each lab session. The results showed that the dimensional and overall levels of anxiety decreased significantly over time in the experimental group but remained stable in the control group. In addition, textual analysis showed that the experimental group students recalled their progress in particularly speaking, listening, writing, reading, vocabulary, grammar, and pronunciation, as well as non-language proficiency progress such as increased cross-cultural knowledge and testing ability. This reminiscing was linked to more frequent positive emotions than negative emotions. The findings and their implications for foreign language anxiety research and foreign language teaching and learning were discussed.